Chemical characterization of Brazilian savannah Byrsonima species (muricis) and their impact on genomic instability and chemopreventive effects - Specian, Ana Flávia L.; Tuttis, Katiuska; Serpeloni, Juliana M.; Ribeiro, Diego L.; Nunes, Higor Lopes; Tangerina, Marcelo M.P. [UNESP]; Sannomiya, Miriam; Varanda, Eliana A. [UNESP]; Vilegas, Wagner [UNESP]; Cólus, Ilce Mara S. (Elsevier, 2023)
The identification of new drugs with few or no adverse effects is of great interest worldwide. In cancer therapy, natural products have been used as chemopreventive and chemotherapeutic agents. Plants from the Brazilian savannah belonging to the Byrsonima genus are popularly known as muricis and have attracted much attention due to their various pharmacological activities. However, there are currently no data on these plants concerning their use as chemopreventive or chemotherapeutic agents in human cell lines. The present study assessed the potential of B. correifolia, B. verbascifolia, B. crassifolia, and B. intermedia extracts as natural alternatives in the prevention and/or treatment of cancer. The chemical constituents present in each extract were analyzed by electrospray ionization–mass spectrometry (ESI-MSN). The mutagenic/antimutagenic (micronucleus assay), genotoxic/antigenotoxic (comet assay), apoptotic/necrotic (acridine orange/ethidium bromide uptake), and oxidative/antioxidative (CM-H2DCFDA) effects of the extracts and their influence on gene expression (RT[sbnd]qPCR) were investigated in nonmetabolizing gastric (MNP01) and metabolizing hepatocarcinoma (HepG2) epithelial cells to evaluate the effects of metabolism on the biological activities of the extracts. The genotoxicity, mutagenicity, and apoptotic effects observed in HepG2 cells with B. correifolia and B. verbascifolia extracts are probably associated with the presence of proanthocyanidins and amentoflavone. In MNP01 cells, none of the four extracts showed mutagenic effects. B. crassifolia and B. intermedia extracts exhibited strong antimutagenicity and enhanced detoxification in HepG2 cells and antioxidant capacities in both types of cells, possibly due to the presence of gallic and quinic acids, which possess chemopreventive properties. This study identifies for the first time B. correifolia and B. verbascifolia extracts as potential agents against hepatocarcinoma and B. crassifolia and B. intermedia extracts as putative chemopreventive agents.
Keywords: Anticancer; Apoptosis; in vitro; Medicinal plant; Mutagenesis; Phytochemicals